Care work and Covid-19: Changes in the daily mobility of women in Santiago, Chile - Catalina Paz Zúñiga-Olave; Marie Geraldine Herrmann-Lunecke (Íconos)
Since 2020, the world has been impacted by the Covid-19 pandemic, causing significant changes in cities, affecting the daily mobility of people, and exacerbating inequalities, particularly for women. Confinement has deepened gender inequality in different dimensions and contexts, whereby many women, as part of their reproductive roles, have assumed more care and domestic work in various spaces, especially at home and in their neighborhoods. This article analyzes the impact of the pandemic on the daily mobility of women linked to their care work in the San Cristóbal neighborhood of Recoleta in Santiago, Chile. With this aim, online in-depth interviews and exploratory maps were conducted with women who perform care work, comparing their work and daily mobility before and during the pandemic. The results show that since the pandemic began, the gender inequality experienced by women has increased, as reflected in their daily activities, particularly in relation to the increase in domestic work and care work. Likewise, a change is observed in the daily mobility of women who perform care work, as they have focused more on walking and movement within their own neighborhoods to cover basic needs.